Impact of Financial Leverage, Investment and Dividend Payments on Likelihood of Financial Distress in Emerging Markets (American Journal of Economics and Business Innovation, 2025)
Financial distress poses a significant challenge for companies around the globe, often resulting from a complex interplay of financial decisions. Understanding the factors that contribute to this risk is crucial for firms seeking to navigate the complexities of financial management. This research explores how these key financial decisions (Financial leverage, investment rate and dividend payment ratio) impact a company’s likelihood of experiencing financial distress. The study initially considered 65 firms listed on the Nairobi Securities Exchange (NSE) as of December 2021. Applying specific inclusion and exclusion criteria, the research narrowed this down to 45 firms that were operational throughout the study period from 2008 to 2021, resulting in 630 firm-year observations in total. The study utilized secondary data from annual financial reports and employed descriptive and inferential statistical methods. The study used panel logistic regression to test hypotheses, providing a robust understanding of the data. The study results specifically indicate a positive and significant effect of financial leverage (β = 0.238, ρ